CONTEXT OF PROTECTION AGAINST DOMESTIC VIOLENCE AND FIGHT AGAINST FIREARMS - LEGISLATIVE FRAMEWORK AND RESOLUTION 1325 IN SERBIA - Spasic, Danijela V; Radovanović, Ivana D (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
Widespread possession of firearms, both legal and illegal, is one of the greatest threats to human security in the modern age. This problem can be linked to various forms of structural and cultural violence, especially for vulnerable and marginalized groups, but it may also be an indicator of socioeconomic differences in society, and a reduced confidence in the ability of institutions to provide them with security. This research shows that, despite the fact that domestic violence and partnership relations do not make up the use of firearms, the widespread possession of firearms is a specific marker in assessing the risk of domestic violence and an institutional response to it in accordance with the Law on the Prevention of Violence in the family. It can be concluded that domestic violence, as a form of gender-based violence, is a complex phenomenon that requires customized measures for its prevention and suppression. Currently, potential barriers to an effective social response to this problem include: the lack of sensitivity of policy makers to the misuse of firearms in the context of gender-based violence; increasing tension in the region and re-focusing on firearms as a means of personal defense. Removing unlawfully held firearms and preventing its abuse requires a long-term strategy, complete and decisive political will and complex solutions.